Genetic Studies of Metabolic Syndrome in Arab Populations: A Systematic Review and Meta-Analysis - Al-Homedi, Zahrah; Afify, Nariman; Memon, Mashal; Alsafar, Habiba; Tay, Guan; Jelinek, Herbert F.; Mousa, Mira; Abu-Samra, Nadia; Osman, Wael (Frontiers in Genetics, 2021)
Background: The metabolic syndrome (MetS) is prevalent in Arabian populations. Several small-scale studies have been performed to investigate the genetic basis of MetS. This systematic review and meta-analysis aimed to examine whether candidate gene polymorphisms are associated with MetS susceptibility among ethnic groups of the Arabian world and to suggest possible directions for future research regarding genetic markers and MetS. Methods: A search was conducted for peer-reviewed articles that examined the genetic association of MetS in Arabian populations in the following databases: Medline, Embase, Scopus, Direct Science, Web of Science, ProQuest, and Google Scholar until March 31, 2021. Articles were eligible if they were case-control studies, which investigated MetS as a dichotomous outcome (MetS vs. no MetS). To assess the quality of the studies, the Q-Genie tool (Quality of Genetic Association Studies) was used. A non-central chi2 (random-effect) distribution was used to determine the heterogeneity (H) of Q and I2 statistics. Results: Our search strategy identified 36 studies that met our inclusion criteria. In most cases, studies were excluded due to a lack of statistical information such as odds ratios, confidence intervals, and p-values. According to the Q-Genie tool, 12 studies scored poorly (a score of ≤35), 13 studies scored moderately (>35 and ≤45), and 12 studies had good quality (> 45 or higher). The most frequently studied genes were FTO and VDR (both included in four studies). Three SNPs indicated increased risk for MetS after calculating the pooled odds ratios: FTO-rs9939609 (odds ratio 1.49, 95% CI: 0.96-2.32); LEP-rs7799039 (odds ratio 1.85, 95% CI: 1.37-2.5); and SERPINA12-rs2236242 (odds ratio 1.65, 95% CI: 1.21-2.24). Meta-analysis studies showed no significant heterogeneity. Conclusions: There were many sources of heterogeneity in the study settings. Most of the studies had low to moderate quality because of sample size and power issues, not considering all potential sources of bias, and not providing details about genotyping methods and results. As most studies were small-scale, aimed to replicate findings from other populations, we did not find any unique genetic association between MetS and Arabian populations.